2006
DOI: 10.1002/ptr.1944
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antihypertensive effect of oral crude stevioside in patients with mild essential hypertension

Abstract: The antihypertensive effect of crude stevioside obtained from the leaves of Stevia rebaudiana (Bertoni) Bertoni (Compositae) on previously untreated mild hypertensive patients was examined. Patients with essential hypertension were submitted to a placebo phase for 4 weeks. The volunteers selected in this phase were randomly assigned to receive either capsules containing placebo during 24 weeks or crude stevioside 3.75 mg/kg/day (7 weeks), 7.5 mg/kg/day (11 weeks) and 15.0 mg/kg/day (6 weeks). All capsules were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…After the interview, blood pressure (BP) and body mass index (BMI) were evaluated. BP (mmHg) was measured as described elsewhere (Ferri et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…After the interview, blood pressure (BP) and body mass index (BMI) were evaluated. BP (mmHg) was measured as described elsewhere (Ferri et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Stevioside and steviol have also been shown to have a direct effect on the beta cells of the pancreas to stimulate the secretion of insulin and improve glucose tolerance that might prove to have a positive impact in the prevention of type 2 diabetes mellitus (Sattigeri, 2012). However, Ferri et al (2006) and others (Chan et al, 2000;Hsieh et al, 2003) reported no significant effect of stevia on glucose homoestasis.…”
Section: Introductionmentioning
confidence: 95%
“…Toxicological reports have also shown that secondary metabolites present in stevia did not have teratogenic, mutagenic (Lemus-Mondaca et al, 2012) or carcinogenic effects. No allergic reactions have been detected following stevia consumption as a sweetener Ferri et al, 2006;Gupta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stevioside and rebaudioside A also exhibit anti-inflammatory and diuretic properties [19], prevent ulceration of the gastrointestinal tract [18,20] and show antihyperglycemic [21][22][23], anti-hypertensive, …”
Section: Main Characteristics Of Steviol Glycosidesmentioning
confidence: 99%